Using An Effective Online Learning Media on Student's Outcome - Sirrul Bari; Faidi Noer (JOEY: Journal of English Ibrahimy, 2022)
This study determines the effect of using online media on student outcomes. This research was conducted at the state Khamas Vocational High School 2020-2021. The research method used was a survey and pre-experiment design with one group pre-test post-test. A number of sample 19 students, were divided into two groups. The instrument used questionnaire and score of pre-test post-test in experimental design. Data analysis techniques using analysis of t-test, and R-square tests. From a value of t-test, it was a significant influence between online method on student learning outcomes obtained at-count value of 9,481 > 1,793 There is an influence of online learning media (X) on learning outcomes (Y), And continued for the know-how of value significant online learning method on student learning outcomes can see from the coefficient of determination test (R2) which means that there is an effect of using online learning media (X) on student learning outcomes of 83,2% while 16,2% of student learning outcomes are influenced by other variables not examined.